Regional developments: Central Asia [in 2025 GFPR] - Akramov, Kamiljon T.; Lambrecht, Isabel B.; Babu, Suresh Chandra; Rajiv, Sharanya (International Food Policy Research Institute, 2025)
Since the countries of Central Asia gained independence in 1991, the region’s food systems have undergone significant transformations shaped by political and economic reforms, institutional shifts, globalization, climate change, and labor migration. This chapter examines how food policy research developed evidence to inform market-oriented reforms and agricultural transformation, ultimately leading to substantial reductions in poverty, food insecurity, and undernutrition, and also assesses the interconnected challenges of climate change, land use, markets and incentives, demographic shifts, socioeconomic trends, and geopolitical factors that face the region in the lead-up to 2050.